RELATIVE EFFICACY OF DIFFERENT INSECTICIDES AGAINST LEAF AINST LEAF FEEDERS ON SOYBEAN CROP ( YBEAN CROP (GLYCINE MAX L. MERRILL) . MERRILL) - DR. RAJEEV GUPTA, RAMBIHARI AHIRWAR, SERVEN VERMA, TARUN SAHU AND (The Bioscan, 2016)
Soybean is a fascinating crop with innumerable possibilities of not only improving agriculture but also supporting industries. In the present investigation, attempts were made to study the relative efficacy of different insecticides against leaf feeders during kharif, 2012 at Research cum Instructional Farm, Indira Gandhi Krishi Vishwa vidyalaya, Raipur, (C.G). It was found that Profenophos 50 EC @ 1250 ml/ha was most effective against caterpillar pests with 1.22 larvae per meter row and the grain yield was 15.450 q/ha with 13.14:1 benefit cost ratio. In Triazophos 40 EC @ 625 ml/ha (2.36 larvae / meter row) with 12.390 q/ha grain yield and 12.30:1 benefit cost ratio. It was followed by Profenophos 50 EC @ 1000 ml/ha (2.01 larvae per meter row) with 11.700 q/ha grain yield and 10.70:1 benefit cost ratio was least economical.